RETRACTED: Ways to use interdisciplinary connections by showing the solution of one insurance problem in teaching - Hajiyeva R.J.; Asgarova B.H.; Haciyev R.N. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001